Nursing Staff's Experiences of Caring for People with Mental Ill-Health in General Emergency Departments: A Qualitative Descriptive Study. (2nd December 2022) - Derblom, Katharina; Molin, Jenny; Gabrielsson, Sebastian; Lindgren, Britt-Marie
Abstract: While people with mental ill-health report unsatisfying experiences and poor treatment in general emergency departments, nursing staff report a lack of adequate knowledge and training. This study describes nursing staff's experiences caring for people with mental ill-health in general emergency departments. A qualitative descriptive design was used and 14 interviews were subjected to qualitative content analysis. Results show that nursing staff are dealing with uncertainty and competing priorities when caring for people with mental ill-health. Nursing staff must both take and be given the opportunity to maintain and develop confidence and independence and need support in promoting mental health recovery.